2019
DOI: 10.1109/access.2019.2940516
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Labeling of Topic Models Using Graph-Based Ranking

Abstract: Generated topic label, an alternative representation of topics learned by topic model, is widely used to help the user interpret the topics more efficiently. A major challenge now is to label a discovered topic accurately in an objective way. This article introduces a novel graph-based ranking model (TLRank), to find a meaningful topic label with high Relevance, Coverage, and Discrimination. The model applies a specific strategy that suppresses or enhances the matrix transition probability according to the tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…The results of the proposed method showed that the use of summaries as labels had apparent advantages compared with the use of words and phrases. He et al [45] built a graph-based ranking model, namely TLRank, that aimed to automatically label every topic produced from topic models. The proposed model used the strategy of enhancing matrix transition probability based on the textual similarity between vertices and the characteristics of vertices (sentences).…”
Section: Automatic Naming Of Topicsmentioning
confidence: 99%
“…The results of the proposed method showed that the use of summaries as labels had apparent advantages compared with the use of words and phrases. He et al [45] built a graph-based ranking model, namely TLRank, that aimed to automatically label every topic produced from topic models. The proposed model used the strategy of enhancing matrix transition probability based on the textual similarity between vertices and the characteristics of vertices (sentences).…”
Section: Automatic Naming Of Topicsmentioning
confidence: 99%
“…Multiple applications utilise the relative information to get the desired outcome. Authors in [25] created a graph-based ranking method for labeling the topic from the terms belonging to the topic and Kullback-Leibler Divergence to select the relevant candidate sentences. The authors created a directed weighted graph using relevance centrality, coverage centrality, and discrimination centrality.…”
Section: B Graph-based Approachesmentioning
confidence: 99%
“…The authors in [26] used an information extraction method based on BM25 and TF-IDF [27] to extract the candidate terms. Authors in [25] rely on graph-based methods for ranking the candidate terms. Authors in [29] consider the categories of extracted Wikipedia documents as candidates.…”
Section: ) Candidate Termsmentioning
confidence: 99%
“…For micro-blogging such as Twitter, text summarization using Text Rank [4] as well as hashtags [38] was also used successfully for topic labeling. Other techniques use word vectors and letter trigram vectors to automatically extract labels for topics [22] as well as unsupervised graph-based methods [1], [19], [44]. In the literature, there have also been proposed hybrid methods that make use of multiple measures to increase the chance to find the correct label for the topic [18].…”
Section: Related Workmentioning
confidence: 99%